2013
DOI: 10.1038/ncomms3123
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus transcytosis and exosome shuttling deliver folate into brain parenchyma

Abstract: Loss of folate receptor-a function is associated with cerebral folate transport deficiency and childhood-onset neurodegeneration. To clarify the mechanism of cerebral folate transport at the blood-cerebrospinal fluid barrier, we investigate the transport of 5-methyltetrahydrofolate in polarized cells. Here we identify folate receptor-a-positive intralumenal vesicles within multivesicular bodies and demonstrate the directional cotransport of human folate receptora, and labelled folate from the basolateral to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
254
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(271 citation statements)
references
References 44 publications
6
254
0
1
Order By: Relevance
“…The exosome solution (2 mg of protein/ml) contained 2.67 ϫ 10 12 particles/ml, which is ϳ35 times higher than the concentration of the exosomes in mouse CSF (7.51 ϫ 10 10 particles/ml). The intraventricularly injected exosomes have been reported to penetrate into brain parenchyma (15). After 2 weeks, there was an approximate 50% reduction in total A␤ and A␤ 1-42 levels and 35% reduction in A␤ 1-38 levels in the hippocampus of the exosome-treated APP mice compared with those infused with vehicle ( Fig.…”
Section: Continuous Exosome Administration Ameliorates A␤ Pathology Amentioning
confidence: 90%
“…The exosome solution (2 mg of protein/ml) contained 2.67 ϫ 10 12 particles/ml, which is ϳ35 times higher than the concentration of the exosomes in mouse CSF (7.51 ϫ 10 10 particles/ml). The intraventricularly injected exosomes have been reported to penetrate into brain parenchyma (15). After 2 weeks, there was an approximate 50% reduction in total A␤ and A␤ 1-42 levels and 35% reduction in A␤ 1-38 levels in the hippocampus of the exosome-treated APP mice compared with those infused with vehicle ( Fig.…”
Section: Continuous Exosome Administration Ameliorates A␤ Pathology Amentioning
confidence: 90%
“…Factors in the blood are also transported across the BCSFB. One example is folate, which is transcytosed and released in exosomes into the CSF to reach the brain parenchyma [55]. This choroidal In addition to being a source of factors via transport and synthesis, the choroid plexus is a sensor of different states.…”
Section: Embryonic and Postnatal Developmentmentioning
confidence: 99%
“…These factors can reach distal areas of the brain via bulk flow of the CSF and can act in both an autocrine and paracrine manner [63,137]. In addition to diffusible factors, exosomes containing signaling factors and non-coding (nc) RNAs, such as long ncRNAs and miRNAs, are present in the CSF [11] and can be choroid plexus-derived [6,55]. Finally, the choroid plexuses also contain a large array of enzymes and act as an enzymatic or metabolic barrier, by modulating the activity and availability of neurotransmitters, peptides, growth factors, hormones, drugs and xenobiotics.…”
Section: Source and Regulated Entry Route Of Factors Into The Brainmentioning
confidence: 99%
“…In fact, other studies suggested that vesicles, biological or synthetic, in blood might invade the brain. 8,9 What is novel and counterintuitive in this present study is that this process might not be unidirectional. Thus, assuming that the mechanism of action of brain-derived microparticles, unveiled in this study, also occurs in humans with trauma brain injury, the authors suggest that the neutralization of the key actor phosphatidylserine, by annexin V or lactadherin, for instance, may have therapeutic value.…”
mentioning
confidence: 72%